Laboratory explorations in biology - Science and Mankind, inc.; Center for Humanities ([Mount Kisco, NY : Center for Humanities, 1987)
Covers the basic ecological concepts of populations, communities, energy flow, and nutrient cycling
Title from title screen
Originally released in 1978 as a slide set
DVD format
Keywords: Ecology -- Technique; Ecology -- Methodology